2020
DOI: 10.1253/circj.cj-19-0843
|View full text |Cite
|
Sign up to set email alerts
|

Japanese Survey of Radiation Dose Associated With Coronary Computed Tomography Angiography ― 2013 Data From a Multicenter Registry in Daily Practice ―

Abstract: Background: Although coronary computed tomography angiography (CTA) is frequently used for identifying coronary artery disease, no studies have investigated the radiation dose in detail in Japan. The aim of this study was to estimate the radiation dose of coronary CTA in Japanese clinical practice and to identify the independent predictors associated with radiation dose. Methods and Results:A multicenter, retrospective, observational study (54 institutions) was conducted for estimating the radiation dose of co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 32 publications
(24 reference statements)
0
6
0
Order By: Relevance
“…Fifth, we lacked a sufficient number of patients who underwent coronary CT angiography using other contrast injection protocols, since our initial study demonstrated the feasibility of the diluted-contrast injection protocol with regard to the homogeneity of intra-coronary CT attenuation compared to the body-weight-based contrast injection protocol ( 6 ). Sixth, there are some concerns about radiation exposure with CT. A 2013 survey in Japan showed that the coronary CT angiography radiation dose was higher than that with routine chest CT ( 29 ). The implementation of strategies to reduce CT radiation exposure (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Fifth, we lacked a sufficient number of patients who underwent coronary CT angiography using other contrast injection protocols, since our initial study demonstrated the feasibility of the diluted-contrast injection protocol with regard to the homogeneity of intra-coronary CT attenuation compared to the body-weight-based contrast injection protocol ( 6 ). Sixth, there are some concerns about radiation exposure with CT. A 2013 survey in Japan showed that the coronary CT angiography radiation dose was higher than that with routine chest CT ( 29 ). The implementation of strategies to reduce CT radiation exposure (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…using a commercially available software program (Ziostation 2; Ziosoft, Tokyo, Japan). The effective scanning dose for the evaluation coronary arteries was calculated from the dose-length product in a dose report in both groups (conversion factor 0.014) ( 9 , 12 ).…”
Section: Methodsmentioning
confidence: 99%
“…After a scout scan, a non-contrast electrocardiogram (ECG)-gated cardiac scan was performed using a prospective ECG-gated technique. After a non-contrast scan, conventional enhanced 320-slice CT was performed with a slice thickness of 0.5 mm and a tube voltage of 120 kV in both groups, using a retrospective ECG-gated with dose modulation technique and decreasing the radiation dose during the systolic phases (if possible) (Table 1) (8)(9)(10). The tube current during the scan was set based on the autoexposure control system (100-750 mA).…”
Section: Ct Protocolmentioning
confidence: 99%
“…Coronary computed tomography angiography (CCTA) is the first-line diagnostic imaging method for children with coronary artery diseases (1)(2)(3), such as those of abnormal origin (4) and coronary aneurysm (5). Reducing radiation and contrast medium doses while providing acceptable image quality (6,7), eliminating motion artifacts (8,9), and maintaining fast and easy operation remains the research focuses. In recent years, through the application of faster gantry rotation and motion correction algorithms such as the Snapshot Freeze (SSF) and wide-detector coverage for the single-beat cardiac scan technique and other technologies, CCTA image quality has been significantly improved.…”
Section: Introductionmentioning
confidence: 99%